PEMANFAATAN LIMBAH BULU AYAM SEBAGAI KOMPOS DAN NPK GROWER UNTUK MENINGKATKAN PERTUMBUHAN DAN PRODUKSI TANAMAN KUBIS (Brassica oleracea L.) - Yuli Retno Winarsih; Raisa Baharudin (UIR Press, 2022)
The purpose of the study was to determine the interaction effect and the main effect of chicken feather waste compost and NPK Grower fertilizer on the growth and production of cabbage (Brassica oleracea var. capitata). This research was conducted at the Experimental Farm of the Faculty of Agriculture, Riau Islamic University. This research was conducted from March to July 2021. This study used a Factorial Completely Randomized Design with two factors. The first factor was the dose of chicken feather waste compost, consisting of 4 levels, namely 0, 150, 300, and 450 g/plant. The second factor is the dose of NPK Grower fertilizer, consisting of 4 levels, namely 0, 7.5, 15, and 22.5 g/plant. If the calculated F is greater than the F table, the further test is continued with the Honest Significant Difference (BNJ) at the 5% level. Parameters observed were plant height, number of leaves, age of shoot formation, age of harvest, plant fresh weight, crop weight, and crop circumference. The results showed that there was a significant interaction between the treatment of chicken feather waste compost and NPK Grower on observations of plant height, number of leaves, age of shoot formation, harvest age, crop weight, and crop circumference. The best treatment was chicken feather waste compost at a dose of 450 g/plant and NPK Grower 22.5 g/plant. The main effect of chicken feather waste compost was real on all observation parameters. The best treatment was chicken feather waste compost at a dose of 450 g/plant. The main effect of NPK Grower is real on all observation parameters. The best treatment for NPK Grower is at a dose of 15 g/plant.